Environmental impact assessment of petrochemical industry using PROMETHEE approach; case study: Arak, Iran - Amooshahi, Solmaz; Pourebrahim, Sharareh; Nejadkoorki, Farhad (Journal of Environmental Engineering and Landscape Management, 2018)
Due to the significant importance of petrochemical industry for Iran’s national economy and the environmental impacts such as wastewater, pollutant emissions, and hazardous wastes, the present study aimed to assess the construction and operation in two phases. Some relevant criteria were distinguished and weighted using Shannon’s entropy, as the objective weighting measures used to measure uncertainty, occurrence probability, severity, and vulnerability, and expert knowledge. The PROMETHEE technique was used due to the presence of large volumes of quantitative and qualitative data and its capability to evaluate the impacts. The steps included forming the evaluation matrix, determining the preference functions and function calculations. The relative desirability of each alternative was measured by calculating the net outranking flows. Finally, the activities were ranked. Based on the results, the main environmental negative impacts are the loss of vegetation cover and land use change, soil erosion and water and air pollution due to activities such as land cleanly shaven, establishment and operation of fuel tanks and drainage changes.